A curious mind [compact disc, unabridged] : the secret to a bigger life - Grazer, Brian, 1953-; Fishman, Charles, 1961- (Simon & Schuster Audio, 2015)
For decades, film and TV producer Brian Grazer has scheduled a weekly 'curiosity conversation' with an accomplished stranger. From scientists to spies, and adventurers to business leaders, Grazer has met with anyone willing to answer his questions for a few hours. These informal discussions sparked the creative inspiration behind many of Grazer's movies and TV shows, including Splash, 24, A Beautiful Mind, Apollo 13, Arrested Development, 8 Mile, J. Edgar, and many others.